Quality of life and functional outcomes following supracondylar humeral fractures in a paediatric population - Taib, Mai Nurul Ashikin; Komahen, Colin; Awang, Mohd Shukrimi; Sharifudin, Mohd Ariff; Abdul Razak, Ardilla Hanim (2016)
The course of recovery in children post injury remains unclear despite recent focus on quality of life (QOL) and func<onal outcomes following trauma. There is a need for accurate assessment of the impact and course of such injuries on a child’s func<onal status and perceived well-being. Determining when and whether or not func<onal outcome and QOL plateaus, will allow health care providers and researchers to focus more intensely on rehabilita<on during period of gain. This will lead to a more adap<ve rehabilita<on aEer plateaus are achieved.